Gamma-Ray Variability from Stellar Wind Porosity in Microquasar Systems - Owocki, S. P. (2010)
In the subclass of high-mass X-ray binaries known as “microquasars,” relativistic hadrons in the jets launched by the compact object can interact with cold protons from the stars radiatively driven wind, producing pions that then quickly decay into gamma rays. Since the resulting gamma-ray emissivity depends on the target density, the detection of rapid variability in microquasars with GLAST and the new generation of Cherenkov imaging arrays could be used to probe the clumped structure of the stellar wind. This paper summarizes recent analyses of how the “porosity length” of the stellar wind structure can set the level of fluctuation in gamma rays. A key result is that, for a porosity length defined by h = L/f, i.e. as the ratio of the characteristic size L of clumps to their volume filling factor f, the relative fluctuation in gamma-ray emission in a binary with orbital separation a scales as (h/πa)1/2 in the “thin-jet” limit, and is reduced by a factor 1/sqrt( 1 + phi a/2L ) for a jet with a finite opening angle phi. For a thin jet and quite moderate porosity length h = 0.03a, this implies a ca. 10% variation in the gamma-ray emission.